Evaluation of Childhood Burns Between 0-15 Ages - Zor, Fatih; Tuğcu, Harun; Açıkel, Cengiz Han; Deveci, Mustafa; İskender, Salim and Toygar, Mehmet and Şengezer, Mustafa (The Bulletin of Legal Medicine, 2008)
The most common burn causes of childhood are due to contact to a hot subject and scalding. The injury generally results from an incident but in 6-20% of the cases there may be neglect. Burns due to neglect are generally scalding injuries. Between 2002-2006, 82 patients whose ages were between 0-15 years old were treated in Gulhane Military Medical Academy Department of Plastic and Reconstructive Surgery and Burn Center. In this study, the patient charts of these 82 patients were retrospectively evaluated. Age, sex, etiology of burn injury, severity of burn injury, hospitalization time mortality and morbidity of the patients were evaluated. Of the patients, 72% had scalding injury, 19% had flame injury with inhalation injury, 5% had electrical injury and 4% had contact injuries. The average total body surface area of burn (TBSA) of the patients was 20.71% and the mortality rate was 17.1%. During childhood period, the detection of the neclegt of the child-sitter or the family is quite difficult. As the patient is not fully able to explain himself, the event is easily misdiagnosed as an accident. The localization and the characteristics of the burn injury will help us to differentiate accident from neglect as an etiology. When an evidence of neglection of children is determined, the judicial responsibility of the health care personnel increases. In such cases the judicial procedures must be started. Key words: Child, burn, neglect